Funding R&D cooperation between firms and universities: The effectiveness of the innosuisse model - Florian Hulfeld; Andrin Spescha; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2024)
This paper investigates the causal effect of funding research and development (R&D) cooperation with public universities on the performance of firms. We use comprehensive firm-level panel data from Switzerland that spans from 2010 to 2022 and covers a broad set of variables including the innovation support received by firms. We examine the effectiveness of the most important public innovation agency Innosuisse, which funds R&D cooperation between firms and universities. To identify the causal effect, we use three newly developed difference-in-differences estimators that allow for arbitrary treatment effect heterogeneity. Because firms selectively apply for funding and Innosuisse selectively funds a subset of applicants, we have a twofold selection problem. To make the parallel trends assumption more plausible, we create a control group based on firms that never applied for Innosuisse funding but otherwise resemble the funded firms. The baseline results show that the funding increases firm sales by 21% and employment by 18% on average over a time window of 5 years. We use specification curve analysis to show that this result holds over numerous important alternative specifications. The funding of R&D cooperation between firms and universities can thus be a potent alternative to more traditional policy instruments like R&D subsidies or tax credits.
Keywords: 330; Research cooperation; Research funding; Corporate success; Switzerland; Forschungskooperation; Forschungsfinanzierung; Unternehmenserfolg; Schweiz